Sustainable viticulture: First determination of the environmental footprint of grapes - Litskas, Vassilis D.; Mandoulaki, Athanasia; Vogiatzakis, Ioannis N.; Tzortzakis, Nikos G.; Stavrinides, Menelaos (My University, 2020)
We present for the first time the environmental footprint (EF) of grapes following the methodology proposed by the EU and life cycle assessment (LCA). We used data from three different production systems, conventional high-or low-input and organic from vineyards on the Mediterranean island of Cyprus. The life cycle inventory (LCI) data were retrieved from the recently released AGRIBALYSE database, and the EF was determined with the Open LCA software. The system boundary was from “cradle to winery door” and the functional unit was 1 ton of grapes delivered to the winery. Organic grape production had the lowest values for most of the 16 EF impact categories. Machinery, fuel, and sulfur production and use were identified as EF hotspots for organic grapes. Fertilizer production and use were identified as EF hotspots for high-input grape production. The EF impact category values for low-input grapes showed similarities with organic production. Future research needs to enrich the LCI databases with data more applicable to the methods and inputs applied in Mediterranean agriculture.
Keywords: LCA; GHG emissions; Energy balance; Water footprint; Indigenous varieties; Viticulture